Earthquakes and robustness for timber structures - Branco, Jorge M. (2009)
Major similarities between robustness assessment and seismic design exist, and significant information can be brought from seismic design to robustness design. As will be discussed, although some methods and limitations considered in seismic design can improve robustness, the capacity of the structure to sustain limited damage without disproportionate effects is significantly more complex. In fact, seismic design can either improve or reduce the resistance of structures to unforeseeable events, depending on structural type, triggering event, structural material, among others.